Bibliometric and visual analysis of suicide in aged people over the past 20 years - Kan, Shao-Kui; Zhang, Ying-Li; Bai, Xue-Xia; Peng, Bo (Frontiers in Psychiatry, 2025)
BackgroundThe rapid aging of the global population presents pressing public health challenges, notably an increase in suicide rates among older adults. Despite this critical issue, there is a scarcity of comprehensive assessments regarding the existing literature on suicide within this demographic. This study seeks to employ bibliometric analysis and knowledge mapping to elucidate prevailing research trends and the overall status of this field.MethodsWe performed a comprehensive computer-based search of the Web of Science Core Collection to identify relevant articles and reviews concerning suicide in the elderly. A bibliometric analysis was conducted, examining various aspects including countries or regions, institutions, authors, journals, keywords, and references. This analysis utilized tools such as CiteSpace, VOSViewer, Pajek, and Excel 365 to facilitate a thorough assessment.ResultsThe analysis covered 1,116 publications from 2005 to 2024. The annual number of publications showed a fluctuating upward trend, with notable decreases in 2007, 2012, 2015, 2017, and 2022, and increases in 2009, 2013, 2016, and 2019, peaking at 121 in 2021, with citations reaching 4,741 in 2022, but declining since then. The United States stands out as the most productive and influential country in the field, boasting the highest number of publications and citations. The country is home to institutions leading in both publication and citation metrics. Prominent authors contributing significantly to this domain include Conwell Yeates, Van Orden Kimberly A., and Waern Margda. Key journals disseminating crucial research are the Journal of Affective Disorders, American Journal of Geriatric Psychiatry, and Lancet. Frequent keywords in this field encompass depression, suicidal ideation, suicide, older-adults, risk, risk factors, prevalence, older adults, ideation, behavior, health, mental health, life, age, people, prevention, symptoms, scale, population, and elderly. The contemporary research emphasis is primarily on identifying, treating, and preventing the suicide risk associated with depression in older adults.ConclusionsThis study highlights the growing research focus on suicide in older adults, particularly related to depression and the identification, treatment, and prevention of suicide risk. The findings underscore the need for targeted prevention strategies and further investigation in this critical public health area.